Sosialisasi Dampak Pernikahan Siri Terhadap Perempuan dan Anak (Pengabdian Kepada Masyarakat di Desa Ancol Kabupaten Tasikmalaya) - Fani, Andifa Dwi; Sidik, Muhammad; Farid, Miftah (Lembaga Pengabdian kepada Masyarakat (LPkM) Universitas Islam Darussalam (UID) | Islamic University of Darussalam Ciamis-Jawa Barat, 2022)
Ancol Village, located in the Cineam District of Tasikmalaya Regency, has implemented community service initiatives. Ancol Village has been selected as the designated target village for community service (PkM). Implementing PkM aims to enhance the quality of Human Resources (HR) by processing and developing the potential of local villages, with the main purpose being to tap into the vast village potential. PkM initiates a village observation process to investigate and assess the village's potential, which will serve as the primary focus for implementing PkM. The programs are systematically designed through consultations among PkM organizations, village officials, and local populations, particularly those who have direct involvement with the programs being developed. The PkM program is executed in a well-balanced manner, beginning with the stages of planning, implementation, and evaluation at the conclusion of each program. The outcomes attained through the comprehensive PkM program encompass the cultivation of community competencies and the facilitation of human capital development, hence augmenting the capacity of local villages. Early childhood literacy programs are implemented to cultivate high-quality human capital.